PENGARUH METODE PEMBELAJARAN ACTIVE LEARNING TIPE QUIZ TEAM TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS KELAS VII SMP PEMBANGUNAN LABORATORIUM UNIVERSITAS NEGERI PADANG - Riri Lestari (JURNAL MANAJEMEN PENDIDIKAN, 2018)
ABSTRACTThis study aims to determine the effect of the Active Learning learning method type Quiz Team on social studies learning outcomes of students in Padang UNP Laboratory Development Middle School by comparing conventional learning models (lecture method). This type of research is Quasy Experiment. The population is class VII students of UNP Padang Laboratory Development Middle School. The total population is 174 students. Sampling by purposive sampling technique. The sample in this study were VIIb grade students as experimental class and VIId grade students as control class with a total sample of 67 students. Data was collected using test results of learning which validity and reliability have been tested. The data is then analyzed using the SPSS and Ms.Excel statistical programs. The hypothesis of this study was tested by the two-average similarity test (t test) at the significance level of 0.05 and dk = 67. The results of the study found that the influence of the quiz team type active learning method on social studies learning outcomes in class VII UNP Padang Development Laboratory. Learning outcomes using the active learning method quiz team type is 72.7 while in the conventional 64 class further hypothesis testing is obtained t count> t table is 8.209> 2.155 with a significance level of 0.05, thus the hypothesis. Thus the H1 hypothesis: "There is a significant influence from the application of Active Learning learning methods on student learning outcomes in social studies class VII in Laboratory Development Middle School Padang State University.Keywords: active learning type quiz team method, learning outcomes